Vulnerability of coastal areas in South in Miri - Zarina, binti Hafitz Mazni (Universiti Malaysia Sarawak (UNIMAS), 2016)
Miri coastal region is very climate sensitive just like any other coastal areas. It is likely to be influenced by climate changes that include sea level rise and monsoon current. It gives bad impact to the coastal areas such as beach erosion, flooding and habitat loss. Hence, this study was conducted to assess the vulnerability of the coast in South Miri using Coastal Integrity Vulnerable Assessment Toolkits (CIVAT) indicator. It focuses on the changes in geomorphological at the beach along South coast of Miri. The geomorphological changes of the beach profiles and shapes were determined by using these two main methods; Beach profiling method adapted from Emery (1961) and Shoreline tracing method adapted from Morton et a!. (1993). The sampling was conducted at 3 selected beaches and each beach has 3 replicates. At the end of this study, the levels of vulnerability for the three beaches in South of Miri were determined.